KONSEP GARAP PAKELIRAN FORMAT TELEVISI - Utami, Citra Dewi (Capture : Jurnal Seni Media Rekam, 2009)
Leather Puppet is a traditional performing theatre . In Its performance, there is some drama elements in which particularly identity with the drama elements in television. Both are separated by the medium of the performance. Television drama is created certainly suitable for television format. Where as wayang kulit or leather puppet has its format namely pakeliran or live performance. In order to switch and match the previous format into television format it must fulfill some criteria of course from the basis of television format.Keyword : leather puppet performing, television format